Wasiat Wajibah Bagi Ahli Waris Yang Bukan Beragama Islam - Soulisa, Mohammad Ibrahim Sidik; Akyuwen, Rory Jeff; Latupono, Barzah (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: Compulsory will is defined as an action taken by a ruler or judge as a state official to compel or give a mandatory will decision for a person who has died, which is given to certain people under certain circumstances.Purposes of the Research: The purpose of this research is to find out and explain how the legal provisions for mandatory wills are regulated in Islamic law, to analyze and discuss the legal consequences of granting a mandatory will for heirs who are not Muslim.Methods of the Research: The type of research used is normative juridical research or library law research, with the type of research being analytical descriptive, the data obtained from normative juridical research is then analyzed and drawn. Using three approaches, namely the Legislative Approach, Case Approach, and Conceptual Approach.Results of the Research: Based on the results of the research carried out, the answer obtained is that there is a legal vacuum regarding the regulation of Wajibah Wills for heirs of different religions in the Compilation of Islamic Law which is used as a legal loophole, then it is necessary to immediately update the Compilation of Islamic Law which will later contain further regulations regarding prohibitions on giving Wajibah will for heirs of different religions so that unity and legal certainty in Islamic inheritance can be realized. Granting a Wajibah Will for Muslim heirs is still possible because it is based on a sense of justice and due to the same religion as the heir, but Wajibah Wills for non-Muslim heirs should not be granted because based on the interpretation of Article 171 letter (c) Compilation of Islamic Law, differences Religion has become an agreement among the ulama to be an obstacle to inheritance. So the concept of a Wajibah Will which takes 1/3 of the inheritance cannot be applied to non-Muslims because they do not have the right to receive an absolute share of the inheritance.